National eHealth Authority (NeHA) - Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
The Government of India has embarked on a path to achieve Universal Health Coverage for all the citizens of India as envisaged by the National Health Policy 2017. To achieve this, the National Health Policy 2017 recommends a paradigm shift from the health system existing in silos to a more comprehensive and a holistic healthcare system, based on the foundation of digital technologies. Digital health technologies are the most powerful tool towards the attainment of Universal Health Coverage. The National Health Policy 2017 recommends the creation of National electronic Health Authority (NeHA) or National Digital Health Authority (NDHA) as a regulatory body for the deployment of digital health interventions in the healthcare sector. The National electronic Health Authority (NeHA) will be the nodal authority to streamline all the efforts needed to develop integrated national health information architecture. The Government of India proposes to establish National electronic Health Authority (NeHA) as a statutory body through a Parliament act called "Digital lnformation Security in Healthcare, Act (DISHA)". The present paper is about the National electronic Health Authority. The document gives a detailed account of its purpose, mission, vision, objectives and functions. An act of parliament called "Digital lnformation Security in Healthcare, Act (DISHA)" under which the National eHealth Authority is proposed to be established is discussed. The role of state electronic Health Authorities is also discussed in brief. The document outlines key challenges for National eHealth Authority to achieve its objectives. This paper also presents a review of International experiences as a guide to establish National electronic Health Authority in India. A brief account of National Digital Health Mission is also given.
Keywords: 330